Mapping International Geopolitical Agenda. Continuing National Conceptions of the Emerging European Crisis - Grasland, Claude; Toureille, Etienne; Leconte, Romain; Severo, Marta (Frontiers in Big Data, 2021)
This study proposes a geopolitical analysis of opinion dynamics %through an interface built for statistical based on a statistical exploration of a press dataset covering 2014–2019. This exploration questions three case studies of geopolitical and international interest: international migration, political borders, and pandemics. Through the framework of geopolitical agenda, the aim of this study is to question the "crisis" status of changes in the media coverage of the three topics in a cross-analysis and multilingual analysis of 20 western European newspapers. It concludes that there is a prevalence of national agendas